PENERAPAN DIGITAL MARKERTING SEBAGAI STRATEGI PEMASARAN UMKM - Safa’atin, Haya Nur; Muhimudin, Muhimudin; Abidin, M.Ihyaul (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2023)
Digital marketing has developed into an effective strategy for micro, small and medium enterprises (MSMEs) to expand market reach and increase sales. The purpose of this writing is to discuss the application of digital marketing as a marketing strategy for MSMEs with a focus on the use of social media, search engines and email marketing in the current digital era. The method used in the research is literature study. The research results are that digital marketing can provide access to global markets at a more cost efficient rate than conventional marketing. In terms of digital marketing, more personal interactions can be achieved with potential customers, this can provide more personalized information and develop closer relationships. In addition, accurate performance measurements can be carried out with real-time tracking and analysis, so that strategies can be adjusted quickly based on the data obtained. Product and service innovation in digital marketing can also open up opportunities for MSMEs to continue to innovate following market trends and ever-changing customer needs. With proper implementation, digital marketing can increase visibility, competitiveness and overall business growth for MSMEs. Keywords; digital marketing, MSMEs, marketing strategy.